Theoretical and methodological principles of land management process - Tretiak А.; Dorosh, Y.; Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2018)
It is substantiated that the basis of the theory of land management is its functions: provision of all interested persons with objective information on the regulation of relations and elaboration of rules for the coordination of state, public and private land interests in the system of land resources management and land use. Keywords. Land management, land management process, land management project, land management procedures, land management activities.